Study on the quality of rice husk ash at different fluidising velocity in a fluidised bed combustor - Rozainee, M.; Ngo, S. P.; Salema, A. A.; Tan, K. G. (2008)

(untitled)
Rice husk ash has a rigid skeleton-like structure due to its high silica content, resulting in a considerable amount of carbon being trapped in the skeleton and cannot be burned or gasified easily. This study was focused on investigating the quality of rice husk ash at different fluidizing velocity during the combustion of rice husk in a fluidized bed combustor (ID 210 mm). When all other parameters are held constant, the optimum fluidizing velocity aids in almost complete combustion, thereby releasing the entrapped carbon for further conversion. This results in ash with consistently low carbon content (less than 2 wt%). The range of fluidizing velocities investigated was from as low as 1.5 Umf to as high as 8 Umf. It was found that the optimum fluidizing velocity was approximately 3.3 Umf as the mixing of rice husk with the bed was good with a high degree of penetration into the sand bed. The resulting ash was fine in size and retained its amorphous form with low residual carbon content (at 2.88 wt %) and minimal sand contamination as shown by the x-ray diffraction analysis.